2010
DOI: 10.3133/sir20105104
|View full text |Cite
|
Sign up to set email alerts
|

Trends in base flow, total flow, and base-flow index of selected streams in and near Oklahoma through 2008

Abstract: Maps showing: 85. Results of Kendall's tau trend analyses of the annual number of days when ix streamflow is (A) equal to zero cubic feet per second and (B) less than 1 cubic foot per second for selected streamflow-gaging stations in and near Oklahoma. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…The window for storm hydrograph duration-the mean length of a runoff peak from a precipitation event-was estimated at 6 days. The mean BFI, or the proportion of streamflow that originates as base flow for 1980-2011, was calculated to be 0.63, which was similar to estimates in Esralew and Lewis (2010). The mean annual base flow for Reach I was calculated to be approximately 69,000 acre-ft (table 9).…”
Section: Reach I Base-flow Separationmentioning
confidence: 48%
“…The window for storm hydrograph duration-the mean length of a runoff peak from a precipitation event-was estimated at 6 days. The mean BFI, or the proportion of streamflow that originates as base flow for 1980-2011, was calculated to be 0.63, which was similar to estimates in Esralew and Lewis (2010). The mean annual base flow for Reach I was calculated to be approximately 69,000 acre-ft (table 9).…”
Section: Reach I Base-flow Separationmentioning
confidence: 48%
“…Though annual precipitation in west central Oklahoma (climate division 4; National Climatic Data Center, 2015) significantly increased over the streamgage period of record, no trends in annual streamflow were apparent at the Carter streamgage (07301500). Annual peak streamflow and annual number of zero-flow days at this streamgage significantly decreased over the period of record while annual base flow and annual base-flow index significantly increased over the period of record (Esralew and Lewis, 2010). The causes of these trends in annual streamflow statistics are not clear.…”
Section: Streamflow Characteristics and Trendsmentioning
confidence: 82%
“…For the study period 1980-2013, about half of the annual surfacewater inflow to Lake Altus was supplied by base flow (as observed at the Carter streamgage [07301500] and computed by using the USGS Groundwater Toolbox [Barlow and others, 2015]), which is the component of streamflow supplied by the discharge of groundwater to streams (Barlow and Leake, 2012) (table 2). However, the total annual base flow and the base-flow index (the ratio of total annual base flow to total annual streamflow) generally have been increasing (while peak flows generally have been decreasing) since the 1960s at the Carter streamgage (07301500), just upstream from Lake Altus (Smith and Wahl, 2003;Esralew and Lewis, 2010). The reasons for these increasing trends in base flow and base-flow index are not clear but could include increases in the number of impoundments (stock ponds and floodwaterretarding structures) or changes in agricultural practices that reduce runoff and promote artificial recharge to the aquifer (Smith and Wahl, 2003).…”
Section: Description Of Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the baseflow volume to the total streamflow volume for the period of analysis is the base-flow index. Although these procedures may not always yield the true base-flow volume of the stream, tests in Great Britain (Institute of Hydrology, 1980), Canada (Swan and Condie, 1983), and the United States (Wahl and Wahl, 1995) indicated that the results of this base-flow separation procedure were consistent and indicative of the true base-flow volume (Esralew and Lewis, 2010).…”
Section: Base-flow Separationmentioning
confidence: 99%